Maxwell time-dependent nanofluid flow over a wedge covered with gyrotactic microorganism: an activation energy process. Issue 1 (31st December 2022) - Waqas, Hassan; Manzoor, Umair; Hussain, Sajjad; Bhatti, M. M.
Abstract : With progressively more sophisticated enhancements in nanotechnology and optimisation, the demand is increasing for more effective and robust heat transfer fluids with significantly greater thermal conductivities than those of traditional ones. The current article deals with the flow of Maxwell nanofluid, over a wedge with the impact of activation energy and motile microorganisms. A transformed construction is recognised to avail an ordinary differential system by exploiting appropriate similarity transformations. The controlling equations for governing flow situations are constructed and addressed using the well-known numerical shooting procedure. For numerical results, bvp4c routine built-in MATLAB software is used. The influence of all the parameters is discussed for the velocity profile, temperature, volumetric concentration profile, andconcentration profile of microorganisms. The progressive valuation of magnetic parameter, wedge angle parameter and bioconvection Rayleigh number reduce the velocity of flow. The basic values of these parameters shall be Pr = 1, Bi  =  EE  =  γ  = 1.0, Nt  =  Nb  = 0.5, Le  =  Ha  =  m  =  Q  = 1, β  = 0.1, A  = 0.5, Nr  = 2, λ 1  = 2, n  = 1, Ω = 5, and α  = π/3. The volumetric concentration of nanoparticles is boosted with higher values of melting parameter and solutal stratification Biot number.